Computergebruikers aan de Groningse universiteit: pendule of torsie tussen centraal en decentraal? - Van Helvoort, Ton (Studium, 2019)
It will be argued that historically costly computers can be seen as a pendulum that sometimes forced the Dutch university to collaborate and take national initiatives, while at a later moment local interests of scientists and administrators were paramount.This pendulum movement arose because computers require capital-intensive investments in which the central government wants to have a decisive say. At the same time, users of computers want to decide for themselves which computer to buy and what to do with it.Since the fifties of the last century, this computer use can be distinguished in automatic calculation—the purpose for which they were designed—and in addition the automation of work processes such as administrative operations. The automation of administrations took place mainly locally, think of the management and administration of the universities, the digitization of libraries and the automation of patient records in hospitals. In parallel with the rise of computers, the government wanted to develop a science and technology policy, that required data input that would be comparable from each of the universities and colleges.The digital university is not the result of technological determinism but of technology—driven by local, interuniversity and national desires and interests. Computers represented the pendulum that balanced academic freedom and university management.